Phytoconstituents and biological analysis of Acorus calamus rhizome of Sindhupalchowk District, Nepal - Pokhrel, Shanta; Chaulagain, Kalpana (BIBECHANA, 2020)
Phytochemical and biological activities of methanolic and hexane extract of Acorus calamus rhizome were carried out. Phytochemical analysis showed the presence of flavonoid, glycoside, saponin, resin and carbohydrates which are responsible for the antibacterial activities. The antibacterial potential was studied against Staphylococcus aureus (gram positive bacteria) and Escherichia coli, Salmonella typhi (gram negative bacteria) using Agar Well Diffusion Method. The activity was shown by both methanolic and hexane extract of Acorus calamus rhizome against both Gram positive and Gram negative bacteria. Antioxidant activity of methanolic extract was evaluated by 2, 2-diphenyl-1-picryl hydrazyl (DPPH) free radical scavenging activity showed potent antioxidant activities with IC50 value 3.74 μg/mL slightly higher than standard ascorbic acid (IC50 = 3.56 μg/mL). BIBECHANA 17 (2020) 104-109